Biocompatible mesoporous hollow carbon nanocapsules for high performance supercapacitors - Wang, Lijian (2021)
A facile and general method for the controllable synthesis of N-doped hollow mesoporous carbon nanocapsules (NHCNCs) with four different geometries has been developed. The spheres (NHCNC-1), low-concaves (NHCNC-2), semi-concaves (NHCNC-3) and wrinkles (NHCNC-4) shaped samples were prepared and systematically investigated to understand the structural effects of hollow particles on their supercapacitor performances. Compared with the other three different shaped samples (NHCNC-1, NHCNC-2, and NHCNC-4), the as-synthesized semi-concave structured NHCNC-3 demonstrated excellent performance with high gravimetric capacitance of 326 F g−1 (419 F cm−3) and ultra-stable cycling stability (96.6% after 5000 cycles). The outstanding performances achieved are attributed to the unique semi-concave structure, high specific surface area (1400 m2 g−1), hierarchical porosity, high packing density (1.41 g cm−3) and high nitrogen (N) content (up to 3.73%) of the new materials. These carbon nanocapsules with tailorable structures and properties enable them as outstanding carriers and platforms for various emerging applications, such as nanoscale chemical reactors, catalysis, batteries, solar energy harvest, gas storage and so on. In addition, these novel carbons have negligible cytotoxicity and high biocompatibility for human cells, promising a wide range of bio applications, such as biomaterials, drug delivery, biomedicine, biotherapy and bioelectronic devices.